Religious Moderation through Friday Sermons: A Collaborative Governance Model in Surabaya Mosques - Ahmad Habibul Muiz; Hammis Syafaq; Achmad Yani; Moehammad Anfa’ul Ulum; Yassirly Amrona Rosyada (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
Friday sermons play a strategic role in shaping public religious understanding among Muslim communities. This study analyzes the collaborative governance of Friday sermons as an instrument for strengthening religious moderation in two urban mosques in Surabaya, namely Masjid Al-Falah and Masjid Ar-Rahmah. Using a qualitative comparative case study, data were collected through in-depth interviews with mosque administrators, media managers, and congregants, supported by documentation of mosque digital media practices. The data were analyzed through condensation, display, coding, thematic categorization, and conclusion drawing. The findings reveal four interconnected dimensions of sermon governance: structural, cultural, substantive, and digital collaboration. These dimensions appear in preacher selection, theme confirmation, sensitivity to congregational characteristics, moderation of sermon content, digital production, and mitigation of sensitive issues. The study concludes that religious moderation in Friday sermons is achieved through collaborative mosque governance that involves administrators, preachers, media teams, and congregants.